Missionary schools in Iraq during the nineteenth century a historical study - Mohammed, Prof.Dr. Naeem Jassim Mohammed (Sulaimani Journal for Humanities, 2026)
The research deals with missionary schools in Iraq during the nineteenth century (a historical study). The research pointed to the most important of those schools and the European countries that established those schools, at a time when Iraq was under Ottoman control in the nineteenth century. The research included four important axes: The first axis referred to a historical overview of the circumstances of the establishment of European communities in Iraq under the rule of Ottoman control in the nineteenth century. As for the second axis, it talked about missionary schools in the state of Baghdad in the nineteenth century. The third axis shed light on the missionary schools in Mosul in the nineteenth century. The fourth axis came under the title of missionary schools in the state of Basra in the nineteenth century. The research relied on a number of Sources, including Arabic and foreign books, and a number of university theses, enriched the research with accurate and important information.
Keywords: missionary schools; Iraq; the nineteenth century